Design and development of an interactive E-book for linear algebra course - Guo, Shuhan (Nanyang Technological University, 2021)
Instructional technologies have been widely used in education to help students become more independent and strategic learners. Various techniques, such as interactive games, reflection on learning journey, have been used to engage, motivate learners. The report begins with a detailed literature review of instructional technology and its application in education field. Book visual representation and interactive animation function design using Adobe InDesign CC are then presented and explained. Using the IIM2007/EE2007 course as an example, this report describes the design and development process of an interactive E-book about Linear Algebra. Finally, limitations and recommendations for future work are discussed.